Construction of an HBPL antibacterial coating on a phase-transition lysozyme-modified titanium surface - Li, Zhangyi; Zhang, Xiangyu; Yu, Hengyang; Zhang, Shuai; Liang, Hong (Frontiers in Oral Health, 2025)
BackgroundIn the field of dental implantation, titanium and its alloys serve as primary materials for implants due to their excellent biocompatibility. However, their insufficient antibacterial properties remain a critical limitation. Bacterial adhesion and subsequent biofilm formation on titanium alloy implant surfaces can trigger peri-implant inflammation, potentially leading to severe complications such as implant failure. To address this challenge, we developed a novel surface modification strategy that endows implants with dual functionality of antibacterial activity and enhanced cellular adhesion, thereby proposing a new approach for preventing and managing peri-implantitis.MethodsA layer-by-layer (LbL) self-assembly technique was employed to construct polyelectrolyte coatings composed of hyperbranched polylysine (HBPL) and hyaluronic acid (HA) on phase-transitioned lysozyme (PTL)-modified titanium surfaces. The surface characteristics were systematically investigated through scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDS). Antibacterial efficacy was evaluated by monitoring bacterial viability and morphological alterations. Cytocompatibility assessments and molecular biological investigations were conducted to examine cellular responses and osteogenesis-related gene expression.ResultsA novel polyelectrolyte coating with favorable biocompatibility and antibacterial properties was successfully fabricated on PTL-modified titanium surfaces. This coating demonstrated significant antimicrobial effects while concurrently promoting osteogenic differentiation to a certain extent.ConclusionThis study presents a dual-functional implant surface coating with combined antibacterial and osteogenic-enhancing capabilities. The developed strategy provides new insights for clinical surface modification of dental implants and offers a promising solution for peri-implantitis prevention and treatment.